Effects of choline on athletic performance and fatigue - Sandage, B. W.; Sabounjian, L. A.; Wuronan, R. (1996)
The data suggest that choline supplementation prior to strenuous exercise may improve performance in certain athletic paradigms as well as reduce fatigue and increase vigor.